USE OF INNOVATIVE TECHNOLOGIES IN THE TRAINING OF FUTURE SKILLED FOOD INDUSTRY WORKERS (Innovative professional education, 2025)
The article describes the relevance of the use of innovative technologies in the professional training of future qualified workers in the food industry. The importance of the use of distance and blended learning in modern conditions as critically important forms of ensuring a continuous educational process in vocational (VET) education is reflected
Keywords: distance learning, innovative technologies, skilled workers, food industry, information and communication technologies, vocational (vocational and technical) education institution